1997
DOI: 10.1046/j.1365-2249.1997.d01-883.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of hu/mu severe combined immunodeficient (SCID) mouse arthritis by local application of human recombinant IL-1β, IL-2 and IL-6

Abstract: The contribution of interleukins produced by most inflammatory cells to chronic arthritis is not well understood. Therefore, we investigated the influence of several human recombinant interleukins (IL‐1β, IL‐2 and IL‐6) on joint swelling, on the inflammatory process, and on serological parameters in a novel animal model of arthritis, the human/murine SCID arthritis. In this model an arthritis is induced by implanting human synovial tissue from patients with rheumatoid arthritis (RA) into the knee joint of mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Notably, however, an increase in IL6 was associated also to treatment with the higher, ineffective dose of anti-TNF treatment. Indeed, while IL6 acts as a pro-inflammatory cytokine in some systems,33 we have previously shown that the local application of recombinant human IL6 does not increase inflammation in hu/mu SCID arthritis 34. In addition, a significant inhibitory effect of IL6 has been demonstrated not only in rat adjuvant arthritis,35 but also in zymosan arthritis induced in IL6 deficient mice 36.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Notably, however, an increase in IL6 was associated also to treatment with the higher, ineffective dose of anti-TNF treatment. Indeed, while IL6 acts as a pro-inflammatory cytokine in some systems,33 we have previously shown that the local application of recombinant human IL6 does not increase inflammation in hu/mu SCID arthritis 34. In addition, a significant inhibitory effect of IL6 has been demonstrated not only in rat adjuvant arthritis,35 but also in zymosan arthritis induced in IL6 deficient mice 36.…”
Section: Discussionmentioning
confidence: 97%
“…Serum IgM was measured by ELISA, as described previously,21 to check for incompleteness of the SCID defect. Mice with > 10 μg/ml IgM22 were excluded from further experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the transplantation of different types of human tissue, i.e. normal SM (six different specimens thus far), lymph nodes, thymus and even cytokine-rich granulation tissue [1,3], induce, at best, inflammatory processes that never rise to the quality and degree of the histological arthritis observed following transplantation of RA-SM (including oligoarticular spreading). Comparative analyses with human and animal tissue transplants may be necessary to formally settle this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the fact that human cells initiate hu/mu SCID arthritis, the disease can be modulated by application of human recombinant cytokines [3]. Host murine cells, on the other hand, can clearly influence the arthritic process, as their activity is modulated by therapy with mAb against murine cytokines [4].…”
Section: Introductionmentioning
confidence: 99%
“…Female C.B.17/lcrCrl‐SCID mice (8–10 weeks of age; Charles River Wiga, Sulzfeld, Germany) were acclimatized for at least 1 week prior to any experimental manipulation and kept in laminar‐flow filter cabinets in the local animal care facility under germ‐free and stable conditions (27 °C, 80% air humidity). To exclude leaky SCID mice, murine serum immunoglobulin levels were examined by ELISA [17]. Mice with immunoglobulin levels >10 µg/ml serum were considered leaky and were not included in our experiments.…”
mentioning
confidence: 99%